Cadmium–1, 4-cyclohexanedicarboxylato coordination polymers bearing different di-alkyl-2, 2′-bipyridines: syntheses, crystal structures and photoluminescence studies. Issue 37 (13th September 2017) - Rosales-Vázquez, Luis D.; Sánchez-Mendieta, Víctor; Dorazco-González, Alejandro; Martínez-Otero, Diego; García-Orozco, Iván; Morales-Luckie, Raúl A.; Jaramillo-Garcia, Jonathan; Téllez-López, Antonio
Abstract : Cd(ii ) polymers, in acetone, can be used as luminescent materials for detection of CH3 CN. Abstract : Four coordination polymers have been synthesized using self-assembly solution reactions under ambient conditions, reacting Cd(ii ) ions with 1, 4-cyclohexanedicarboxylic acid in the presence of different 2, 2′-bipyridine co-ligands: [Cd(H2 O)( e, a-cis -1, 4-chdc)(2, 2′-bpy)]·H2 O n (1 ); [Cd2 (H2 O)2 ( e, a-cis -1, 4-chdc)2 (4, 4′-dmb)2 ] n (2 ); [Cd( e, a-cis -1, 4-chdc)(5, 5′-dmb)]·H2 O·CH3 OH n (3 ) and [Cd( e, e-trans -1, 4-chdc)(4, 4′-dtbb)]·CH3 OH n (4 ), where 1, 4-chdc = 1, 4-cyclohexanedicarboxylato, 2, 2′-bpy = 2, 2′-bipyridine, 4, 4′-dmb = 4, 4′-dimethyl-2, 2′-bipyridine, 5, 5′-dmb = 5, 5′-dimethyl-2, 2′-bipyridine and 4, 4′-dtbb = 4, 4′-di- tert -butyl-2, 2′-bipyridine. Crystallographic studies show that compound1 has a 1D structure propagating along the crystallographic b -axis; the Cd ion in1 is six-coordinated with a distorted-octahedral coordination sphere. Compound2 has two crystallographic different Cd ions and both are six-coordinated with a distorted-octahedral coordination sphere. Compound3 exhibits a seven-coordinated Cd ion having a distinctive distorted-monocapped trigonal prismatic geometry. In compound4, the Cd ion is also seven-coordinated in a distorted monocapped octahedral geometry. Compounds2, 3 and4 possess rhombic-shaped dinuclear units (Cd2 O2 ) as nodes to generate larger cycles made up of four dinuclear units, a Cd4 motif, bridged by four 1, 4-chdc ligands, accomplishing, thus, 2D structures. Remarkably, in compound4 the 1, 4-chdc ligand conformation changes to the equatorial, equatorial trans, unlike the other compounds where the bridging ligand conformation is the more typical equatorial, axial cis . The solid state luminescence properties of1–4 were investigated; polymers3 and4 exhibited a strong blue emission ( λ em = 410–414 nm) compared to1 and2 ; structure-related photoluminescence is attributed to the degree of hydration of the compounds. Furthermore, Cd-polymer3 suspended in acetone allows the fluorescence selective sensing of acetonitrile over common organic solvents such as alcohols and DMF, based on turn-on fluorescence intensity with a limit of 53 μmol L −1 .